2014
DOI: 10.1007/s11033-014-3169-7
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10-1082 gene polymorphism is associated with papillary thyroid cancer

Abstract: The etiopathogenesis of thyroid cancer has not been clearly elucidated although the role of chronical inflammation and the imbalance between pro- and anti-inflammatory cytokines may play a role in the etiology. The aim of the present study was to investigate whether cytokine gene polymorphisms are associated with papillary thyroid cancer (PTC), and to evaluate the relationship between genotypes and clinical/laboratory manifestation of PTC. Tumor necrosis factorα (TNFα) G-308A (rs 1800629), interleukin-6 (IL-6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The involvement of IL-10 in inflammatory processes during infection and autoimmunity has been established by several previous studies (Ying et al, 2011;Chen et al, 2013;Qin et al, 2013). Because of its immunosuppressive and anti-inflammatory properties, it has been hypothesized that IL-10 contributes to tumor escape from immune surveillance, thereby enhancing tumor growth (Çil et al, 2014;Qi et al, 2014;Fei et al, 2015;Yu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of IL-10 in inflammatory processes during infection and autoimmunity has been established by several previous studies (Ying et al, 2011;Chen et al, 2013;Qin et al, 2013). Because of its immunosuppressive and anti-inflammatory properties, it has been hypothesized that IL-10 contributes to tumor escape from immune surveillance, thereby enhancing tumor growth (Çil et al, 2014;Qi et al, 2014;Fei et al, 2015;Yu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Respectively, alleles A and G of this SNP seem to be associated with low and high levels of IL-10 production 10 . Several recent studies have shown that this SNP increases the susceptibility to digestive cancer, schizophrenia, gastric cancer, type-2 diabetes mellitus, and thyroid cancer 11 - 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Article involving more than one independent study group was analyzed separately. Altogether, 78 articles with 87 study groups (45569 cancer patients and 57990 controls) were eligible for the association between IL-6 gene -174G/C variant and cancer 6 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 , and 6 articles with 9 study groups (1727 study subjects) were eligible for circulating IL-6 changes across -174G/C genotypes …”
Section: Resultsmentioning
confidence: 99%